BASLAWÍSH KLASS OQÍWSHÍLARÍN XALÍQ AWÍZEKI DÓRETPELERI TIYKARÍNDA TÁRBIYALAWDÍŃ ÁHMIYETI - Berdibaeva, G.J.; Berdibaeva, Z.J. (ILIM hám JÁMIYET, 2022)
The article is aimed at revealing the importance of educating elementary school students on the basis of folklore. At the same time, examples of folk art, which are convenient for elementary school students, have been touched upon. The educational effect has been revealed of with the help of the lullabies, quick sayings, and riddles.